Rare causes of pediatric anaphylaxis due to obscure allergens - Melethil, Shajitha; Yousef, Ejaz (Frontiers in Allergy, 2024)
This review provides a comprehensive overview of rare causes of pediatric anaphylaxis related to obscure allergens. Anaphylaxis, a severe hypersensitivity reaction, can occur without typical symptoms, posing diagnostic challenges, especially in children. Idiopathic anaphylaxis, where no trigger is identified despite thorough evaluation, is notably challenging in this population. This review synthesizes current literature, highlighting obscure triggers such as food additives, spices like fenugreek, and cross-reactive allergens, including lupine and gelatin. These allergens are often overlooked and can lead to misdiagnosis of idiopathic cases. Understanding these uncommon triggers is crucial for clinicians to ensure accurate diagnosis and effective management of pediatric anaphylaxis, emphasizing the need for heightened clinical awareness and further research. This review raises awareness among health care providers about these lesser-known causes, aiming to improve outcomes and quality of life for pediatric patients at risk of anaphylactic reactions.